2021
DOI: 10.1039/d1ee01336j
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the solubility properties of polymer donors for high-performance layer-by-layer processed organic solar cells

Abstract: Developing high-performance polymer donors are highly demanded to fulfil the potential of the layer-by-layer (LBL) processed organic solar cells (OSCs). In this study, we present an effective method to develop...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…Very recently, LbL-PSCs have attracted more attention with acceptable PCE in comparison with that of BHJ-PSCs. [6,[14][15][16][17][18][19][20][21] Here, we summarized the typical works on comparative study about LbL and BHJ-PSCs; the key photovoltaic parameters of LbL and BHJ-PSCs are listed in Table 1. After well-analyzing the photovoltaic parameters, it is difficult to give a definitive conclusion on the advantages of LbL-PSCs or BHJ-PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, LbL-PSCs have attracted more attention with acceptable PCE in comparison with that of BHJ-PSCs. [6,[14][15][16][17][18][19][20][21] Here, we summarized the typical works on comparative study about LbL and BHJ-PSCs; the key photovoltaic parameters of LbL and BHJ-PSCs are listed in Table 1. After well-analyzing the photovoltaic parameters, it is difficult to give a definitive conclusion on the advantages of LbL-PSCs or BHJ-PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Such a structure was defined previously as a quasiplanar heterojunction (Q-PHJ). [32][33][34][35] In the Q-PHJ structure, each component of the bilayer can be separately optimized, which facilitates better control of the active layer morphology and targeted analysis. This kind of structure achieves efficient exciton dissociation without adversely affecting the transports of the carriers in either the polymer donor or acceptor layers, and the carrier recombination could be reduced significantly.…”
Section: Introductionmentioning
confidence: 99%
“…283 Ning et al reported the highest PCE (17.59%) of the LBL-deposited OSCs by developing an insoluble donor, PNTB6-Cl, in CF solvent due to its stronger intermolecular interactions and shorter π–π stacking distance. 284 Although the LBL process makes the vertical phase separation, the LBL-deposited active layer is mixed by the lamination process and returned to an amorphous form. However, the insoluble PNTB6-Cl induced high enhancement while maintaining effective vertical pathways with N3.…”
Section: Fabrication Processes For Industrializationmentioning
confidence: 99%
“…However, the insoluble PNTB6-Cl induced high enhancement while maintaining effective vertical pathways with N3. 284…”
Section: Fabrication Processes For Industrializationmentioning
confidence: 99%